Repeated-dose toxicity and immunogenicity evaluation of a recombinant subunit COVID-19 vaccine (ZF2001) in rats - Sun, Ruimin; Xia, Lijuan; She, Guangbiao; Li, Jinrong; Wang, Yiru; Chen, Yunxiang; Yang, Qian; Zhang, Siming; Liu, Fang; Chen, Ying; Zhang, Liyan; Zhang, Chengda; et al. (Frontiers in Cellular and Infection Microbiology, 2025)
Coronavirus disease 19 (COVID-19), caused by severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2), had given rise to a massive epidemic. Owing to the high morbidity and mortality of COVID-19 and the lack of effective therapies, safe and effective vaccination is the optimum choice for controlling this epidemic and preventing infection. The protein subunit vaccine ZF2001, which targets the receptor-binding domain (RBD) protein of SARS-CoV-2, has a significant protective effect against COVID-19. At the beginning of the COVID-19 epidemic, to promote the early approval of ZF2001 for clinical trials by the National Medical Products Administration of China (NMPA), a comprehensive evaluation of its toxicity in vivo was warranted. In the present study, a major part of the above series of studies, we evaluated the safety, immunogenicity and efficacy of the ZF2001 vaccine for the first time in adult Sprague Dawley (SD) rats. The male and female rats were administered three doses of the ZF2001 vaccine (25 μg or 50 μg NCP-RBD protein/dose, containing the aluminum-based adjuvant). The safety profile of ZF2001 was assessed by observing the general health status, local toxicity at the site of administration, immunotoxicity, immunogenicity, blood chemistry and hematology parameters in SD rats. In general, our results indicated that the ZF2001 vaccine did not induce significant systemic toxicity in rats, with a no-observed adverse effect level (NOAEL) of 50 μg NCP-RBD protein/rat. Moreover, the ZF2001 vaccine showed good immunogenicity by inducing the production of specific IgG antibodies in rats after three consecutive immunizations. In addition, histological examination revealed recoverable inflammatory changes in quadricep muscles and adjacent lymph nodes at the vaccine injection site. In summary, our systematic toxicology study proves the safety, tolerability and immunogenicity of the ZF2001 vaccine, which further supports the results of clinical trials of ZF2001.